The comparison of strength and endurance in trunk stabilizer muscles between healthy people and subjects with patellofemoral joint pain syndrome - Farahnaz Ghafari Nejad; Leyla Afrazian; Fatemeh Jahanbakhsh; Leyla abbasi (Vesnu Publications, 2012)
Introduction: Trunk is a base for rotational movement patterns in shoulder and pelvic girdles and maintains the stabilization of spine, pelvis and lower extremities during movements. Dynamic trunk stability is provided by the muscles and dysfunction of them could cause musculoskeletal problems in other parts of the body. Patellofemoral pain syndrome (PFPS) is one of the most common knee disorders. Due to the prevalence of this disease in young people and the function of trunk muscles to stabilize the proximal joints for distal parts movement, it seems necessary to examine the importance of trunk stabilizers muscles on PFPS. The purpose of this study was to compare the strength and endurance in trunk stabilizer muscles between healthy people and subjects with PFPS. Materials and Methods: Fifteen participants with PFPS and fifteen healthy subjects were recruited in this study. Trunk muscles strength and endurance including trunk extensors, trunk flexors, right and left lateral trunk flexors were compared in two groups. The patient's pain intensity was measured by Visual Analog Scale. Results: Strength and endurance of trunk stabilizer muscles in patients with patellofemoral pain syndrome in flexor muscles (P = 0.001), extensor (P = 0.005) and right (P = 0.016) and left (P = 0.058) lateral flexors was significantly lower than the healthy group. No significant correlation was determined between pain intensity and decreased trunk muscle endurance. Conclusion: It seems necessary to be considered trunk muscle strength and endurance exercise in common rehabilitation program for PFPS treatment. Keywords: Endurance, Trunk muscles, Patellofemoral pain syndrome